Medial Chances and Challenges for the British Monarchy: On the Reciprocal Relation between a Post-Political Institution and its Media Representations (KULT_online, 2017)
Mandy Merck‘s edited volume The British monarchy on screen comprises seventeen articles dealing with the multifaceted layers of media representation of the British monarchy. Its sections are devoted to studying topics covering the interactions between monarchy and media in Victorian times as well as the role of the empire and commonwealth relations within filmic depictions of the monarchy, leading to forms of popular participation in royal events and contemporary Anglophone cinematic takes on the British monarchy. The collection thus offers new perspectives on an ancient institution whose popularity indicates its enduring importance for British culture and society. The thematic and material diversity in conjunction with the methodological clarity of the featured contributions offers an interesting read, providing several points of departure for fruitful future research both in the realm of media studies and royal studies.